Inflammatory bowel disease in Mexico: Epidemiology, burden of disease, and treatment trends - Yamamoto Furusho, J. K.; Bosques Padilla, Francisco Javier; Charúa Guindic, L.; Cortés Espinosa, T.; Miranda Cordero, R. M.; Saez, A.; Ledesma Osorio, Y. (2020)
Introduction and aims: There is no systematized information for determining/monitoring the burden of inflammatory bowel disease in Mexico. The aim of the present study was to estimate the annual burden of inflammatory bowel disease on the Mexican National Healthcare System, by number of patients seen, hospitalizations, and specific deaths, stratified into age groups. Materials and methods: Utilizing specific databases of the Mexican National Healthcare System registries coded as ICD-10: K50 and K51, we retrieved and analyzed the data corresponding to the patients seen and hospitalized in 2015, stratified by age group, as well as the specific deaths. Treatment trends among physicians were also examined. Results: In 2015, 5009 women (8.1) and 4944 men (8.4) with Crohn’s disease received medical attention (prevalence of cases seen) and 35.1% of those patients were ≥50 years of age. In that same period, 17,177 women (27.7) and 15,883 men (26.9) with ulcerative colitis wereseen and 31.6% of those patients were ≥50 years of age. The hospitalized cases (prevalence ofhospitalized cases) were 1097 patients (0.91) with Crohn’s disease and 43.7% of those patientswere ≥50 years of age; and 5345 patients (4.42) with ulcerative colitis and 47.6% of thosepatients were ≥50 years of age. Deaths (specific mortality rate) were: 32 women (0.52) and 36men (0.50) due to Crohn’s disease, and 267 women (4.31) and 186 men (3.15) due to ulcerativecolitis.Conclusions: Inflammatory bowel disease is a burden on the health of Mexican adults and theMexican National Healthcare System, and it is expected to increase over the next 15 years